Analyzing the international competitiveness of the industry in Portugal, Ireland, Greece and Spain using revealed comparative advantages (RCA) indicators - Jens Oelgemöller (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2012)
This paper sheds light on the export structure of the four European countries Portugal, Ireland, Greece and Spain, the so called PIGS countries. These countries were all hit by the economic downturn in the course of the financial crisis and have been struggling with the national debt crisis and recession. One way to identify sectoral international competitiveness is provided by the revealed comparative advantage index developed by Balassa (RCA 1). This indicator evolved through several studies, for example by the German council of experts (RCA 2). Both indicators suggest that the dominant advantages of Portugal and Greece can be found within agriculture and natural resources. The dominant export sectors are also located there. Ireland stands out from the other PIGS, as high-tech and medical/chemical products occur in the top sectors. Spain's top export sectors do not have the competitiveness that one might expect. Furthermore, the Balassa-Index is transformed to a standardized and symmetric index RSCA, which has values ranging from minus one to plus one and is plotted against the trade balance index (TBI). Thus, information on country trade structure can be depicted. Ireland is to a certain extent dependent on the world market, without having a sound national industry as a basis. Gaining from the global economy through export growth will not have a major impact in Greece and Portugal. Spain does have competitive sectors and a degree of specialization, but the most important sectors are less competitive. Finally, the level of specialization (beta-specialization) and the specialization-process (specialization) are identified by a short OLS-estimation. The beta-specialization does not indicate high degrees of specialization in those countries. According to the specialization, there do not seem to be significant specialization or de-specialization trends since 1995.
Keywords: F14; 330; Revealed Comparative Advantages; Trade Specialization; Product Mapping